The Effect of Net Profit Margin And Return On Asset on Financial Distress of Coal Mining Sector Companies Registered In IDX Period 2014 – 2018 - Indah Setyowati; Imam Susanto (Neraca : Jurnal Akuntansi Terapan, 2020)
This study aims to examine the effect of Net Profit Margin, Return On Asset, on Financial Distress that are calculated using the Altman Z-score. The population in this study is the coal mining companies listed on the Indonesia Stock Exchange period 2014 – 2018. Sampling in this study uses the Purposive Random Sampling method in order to obtain a sample of 30 samples from 6 companies. This research uses a quantitive approach to the type of collaborative research. The data used in the form of company financial statement obtained from the Indonesia Stock Exchange. The data is then analyzed using multiple linier regression methods with SPSS version 26 . The results of the analysis show that partially Net Profit Margin has a negative effect and significant on the Financial Distre. This is evidenced through the t test, where t count is smaller than t table (-1,738 < 2,0518) and Return On Asset has a positive and significant effect on Financial Distress. This is evidenced through the t test, where t count is bigger than t table and is (4,633 > 2,11991). Simultaneously, Net Profit Margin, Return On Asset has a significant effect on the Financial Distress this is indicated by the significance of the F test value of 0,000 smaller than 0,05